REGULATION AND DEVELOPMENT OF TERRITORIES IN LAND PROPERTIES - REGULATORY ASPECTS AND PROBLEMS - G. Velkovska (Trakia Journal of Sciences)
The regulation of territories inland properties is a specific technological and legal process, which is carried out through the tools of detailed spatial planning. The detailed development plans regulate streets, neighborhoods, and land properties for construction and for meeting other needs without construction of the respective land properties. The task of the settlement is to prepare the necessary conditions on the territory in order to make possible the realization of the construction itself. In this sense, it can be said that both processes are interrelated, but the leading and necessary role of the process of settlement of land in the land. The unifying moment in both processes is their legal regulation, which takes into account in detail the specifics of the specific territories and on this basis approves the specific parameters of the settlement and construction. The settlement of a land property determines its boundaries to a street, road or alley (face of the property) and to the neighboring land properties (side and to the bottom of the property). The settlement of each property also determines the type, manner, character, lines and value indicators of construction in the land property. The purpose of the article is to present and analyze some normative aspects and problems related to the regulation and construction of territories in land properties. The main research method used in the article is normative analysis. On the basis of the performed normative analysis some imperfections of the normative regulation are summarized and as a final result way for overcoming these imperfections are suggested in the conclusion. For the purposes of the analysis, opinions of authors working in this field were also used.